2000
DOI: 10.1007/s003830000423
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic adrenal hemorrhage in children: an indicator of visceral injury

Abstract: Adrenal hemorrhage (AH) was identified in 1% of 313 children admitted to the trauma unit with abdominal or thoracoabdominal blunt trauma within a 10-year period (1989-1999). Ultrasound examination was useful as a first diagnostic measure in stable children, but computed tomography (CT) is considered to be a better diagnostic tool. Associated visceral injury is common, and liver trauma was present in all 3 cases. Lesions are mainly right-sided, but left-sided or bilateral injuries have also been reported. A few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…However, the reported incidence of ADGI in post mortem studies ranged between 7% and 26% of deaths secondary to severe thoracoabdominal injuries [12]. ADGI seldom occurs as an isolated injury, and its diagnosis remains difficult due to the absence of clinical manifestation and biochemical investigation, and also the position of the adrenal glands, surrounded by protective soft tissue structure [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported incidence of ADGI in post mortem studies ranged between 7% and 26% of deaths secondary to severe thoracoabdominal injuries [12]. ADGI seldom occurs as an isolated injury, and its diagnosis remains difficult due to the absence of clinical manifestation and biochemical investigation, and also the position of the adrenal glands, surrounded by protective soft tissue structure [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, the rate of adrenal hematoma on the right side of the body was more than that on the left side (Luchtman & Breit qand, 2000;Gabal et al, 2000;Shwartz et al, 2000). In contrast in the current study, adrenal hematoma was more frequent on the left side of the body (61%) than on the right side (37%).…”
Section: Discussionmentioning
confidence: 89%
“…For example, Luchtman and Breit qand (2000) reported 3 cases with adrenal hematoma in tandem with liver trauma and suggested the formation of adrenal hematoma as an index for the relevant visceral injuries. Likewise, in the study by Gabal et al (2000), adrenal hematoma was reported in association with liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…In an autopsy series of blunt abdominal trauma victims a frequency of 7% [1] to 26% [10] was reported. It has been more thoroughly studied in children, in whom it is a frequent finding in the battered child syndrome (3-5%) [3,4]. It is then mostly unilateral and right-sided (80%), associated with chest injury (67%) or other abdominal injuries (50%) [3,4,9].…”
Section: Discussionmentioning
confidence: 99%
“…It is usually unilateral and right-sided [1,2], is asymptomatic and frequently associated with other abdominal and thoracic lesions [1][2][3][4]. Bilateral haemorrhage is rare but life threatening because of the risk of acute adrenal insufficiency [5,6].…”
Section: Introductionmentioning
confidence: 99%